An international qualitative study exploring patients' experiences of cutaneous leishmaniasis: study set-up and protocol. Issue 6 (15th June 2018) - Erber, Astrid Christine; Arana, Byron; Bennis, Issam; Ben Salah, Afif; Boukthir, Aicha; Castro Noriega, Maria del Mar; Cissé, Mamoudou; Cota, Gláucia Fernandes; Handjani, Farhad; Kebede, Mairie Guizaw; Lang, Trudie; López Carvajal, Liliana; et al.
Abstract : Introduction: Lack of investments in drug development, lack of standardisation of clinical trials and the complexity of disease presentations contribute to the current lack of effective, safe and adapted treatments for cutaneous leishmaniasis (CL). One aspect concerns outcomes affecting patients' quality of life (QoL): these are hardly assessed in trials, despite potential functional and/or aesthetic impairment caused by CL, which typically affects disadvantaged and vulnerable people living in rural areas. Here, we describe the approach used to bring perspectives of patients with CL into designing and assessing treatments. Methods and analysis: This international qualitative study uses interviews with patients to explore their experiences with CL to (1) elicit outcomes and eligibility criteria for clinical trials important to them and (2) to better understand their needs and views about the disease and their requirements and expectations from treatment. Here, we describe the set-up of this collaborative study and the protocol. Data collection is ongoing. The protocol includes study design, preparation, conduct and analysis of individual interviews with approximately 80 patients in seven countries (Burkina Faso, Brazil, two sites in Colombia, Iran, Morocco, Peru and Tunisia) where CL is prevalent. Principal investigators and sites were selected through an open call, and two workshops were organised for protocol development and training in conduct and analysis of qualitative health research. Patient recruitment aims at covering a maximum variation of experiences. Transcripts will be analysed to identify outcomes and eligibility criteria as well as further topics that are expected to emerge from the interviews, such as direct and indirect costs related to CL, its psychological impact, preferred modes of drug administration and traditional treatments. Ethics and dissemination: The study received ethical approval by the responsible committees of each of the participating institutions. Findings will be disseminated through publication in peer-reviewed journals, scientific meetings and to participants and their communities.